Molten salt ion exchange route to ZnGaNO single crystal nanorods for improved CO2 photoreduction to CH4. Issue 5 (8th December 2014) - Zhou, P.; Yan, S. C.; Zou, Z. G.
Abstract : A molten salt growing to single crystal ZnGaNO nanorods with high performance for CO2 reduction. Abstract : Single crystal ZnGaNO nanorods, exhibiting a high performance in CO2 reduction due to the high specific area and low defect density, were synthesized by a molten salt growth route.